Raw material of high-wettability battery diaphragm as well as preparation method and application of raw material
By swelling and polar monomer grafting treatment in the raw materials of the battery separator, the problem of insufficient wettability of the traditional separator is solved, and the circulation capacity retention and rate performance of the battery are significantly improved.
Patent Information
- Application Number
- CN202510046964.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-15
AI Technical Summary
Due to its non-polar nature, traditional battery separators make the infiltration speed and low liquid absorption rate when in contact with the electrolyte, which limits the high performance development of the battery.
By mixing a swelling agent with a polyolefin powder, swelling treatment is performed, and then under the action of an initiator and a polar monomer, the polar monomer is grafted onto the surface of the polyolefin to form a modified polyolefin, thereby improving the wettability of the separator.
It improves the wettability and ionic conductivity of the diaphragm, enhances the retention rate and rate performance of the battery, and improves the stability and life of the diaphragm.
Smart Images

Figure BDA0005238752330000071 
Figure BDA0005238752330000111 
Figure BDA0005238752330000121
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular provides a raw material for a high-wettability battery separator, a preparation method and use thereof, wherein the wettability of the separator is improved by chemical modification. Background Art
[0002] With the development of society, the rapid rise of electric vehicle technology and smart wearable equipment, the demand for high-performance batteries is increasing. Battery separators are key components in batteries, and their performance directly affects the overall performance of the battery. At present, commercial batteries have higher requirements for the cycle capacity retention rate and rate performance of batteries. Therefore, improving the ionic conductivity of the separator and then improving the cycle capacity retention rate and rate performance of the battery has become a direction for the development of the separator market. Due to its non-polar characteristics, traditional separators have a slow wetting speed and low liquid absorption rate during contact with the electrolyte, which leads to greater limitations in the battery application process, which further inhibits the development of high-performance batteries. Summary of the invention
[0003] The purpose of the present invention is to provide a raw material for a high-wettability battery separator and a preparation method and use thereof, so as to improve the lyophilicity of the battery separator and its ability to quickly absorb electrolyte, thereby creating a high-performance battery.
[0004] The first aspect of the present invention is achieved as follows: A method for preparing raw materials for a highly wettable battery separator, comprising: mixing a swelling agent with a polyolefin powder, wherein the melt index of the polyolefin powder is 0.2 g / 10 min to 1.5 g / 10 min, and swelling the polyolefin powder to obtain a swollen polyolefin; mixing an initiator and a polar monomer with the swollen polyolefin; and increasing the temperature to graft the polar monomer onto the surface of the swollen polyolefin to form a modified polyolefin.
[0005] For example, the swelling agent includes one or more of toluene, xylene, and ethyl acetate.
[0006] For example, the polyolefin powder includes one or more of polyethylene, polypropylene, polytetrafluoroethylene, polyamide, polyvinyl chloride, polyvinylidene fluoride, polyaniline, polyimide, polyethylene terephthalate, and polystyrene.
[0007] For example, the initiator includes one or more of DCP, BPO, polyvinyl alcohol, ammonium persulfate, and persulfate chloride.
[0008] For example, the polar monomer includes one or more of acrylic acid, maleic anhydride, ethyl methacrylate, hydroxyethyl methacrylate, butyl hydroxyacrylate, and dopamine.
[0009] For example, the step of mixing the initiator, the polar monomer and the swollen polyolefin further includes: mixing a dispersant, the initiator, the polar monomer and the swollen polyolefin.
[0010] For example, the dispersant includes one or more of water, acetone, and white oil.
[0011] For example, the mass ratio between the polyolefin powder and the swelling agent is 100:(5 to 50).
[0012] For example, the mass ratio between the polyolefin powder and the initiator is 100:(0.2 to 5).
[0013] For example, the mass ratio between the polyolefin powder and the polar monomer is 100:(10 to 100).
[0014] For example, the mass ratio between the polyolefin powder and the dispersant is 100:(50 to 600).
[0015] For example, the molecular weight of the polyolefin powder is 100,000 to 1,000,000.
[0016] For example, the particle size of the polyolefin powder is 100 mesh to 300 mesh.
[0017] For example, the grafting rate of the modified polyolefin is 16% to 80%.
[0018] The second aspect of the present invention is achieved as follows: a raw material for a high wettability battery separator, comprising: a modified polyolefin, the modified polyolefin comprising a swollen polyolefin and a polar monomer, the polar monomer being grafted to the surface of the swollen polyolefin, and the swollen polyolefin comprising a polyolefin powder, the melt index of the polyolefin powder being 0.2 g / 10 min to 1.5 g / 10 min.
[0019] For example, the polyolefin powder includes one or more of polyethylene, polypropylene, polytetrafluoroethylene, polyamide, polyvinyl chloride, polyvinylidene fluoride, polyaniline, polyimide, polyethylene terephthalate, and polystyrene.
[0020] For example, the polar monomer includes one or more of acrylic acid, maleic anhydride, ethyl methacrylate, hydroxyethyl methacrylate, butyl hydroxyacrylate, and dopamine.
[0021] For example, the mass ratio between the polyolefin powder and the polar monomer is 100:(10 to 100).
[0022] For example, the molecular weight of the polyolefin powder is 100,000 to 1,000,000.
[0023] For example, the particle size of the polyolefin powder is 100 mesh to 300 mesh.
[0024] For example, the grafting rate of the modified polyolefin is 16% to 80%.
[0025] The third aspect of the present invention is achieved as follows: a high wettability battery separator, comprising: the raw materials of the high wettability battery separator mentioned above.
[0026] The present invention has at least the following technical effects:
[0027] The battery separator prepared by the above-mentioned material has abundant polar groups, which is beneficial to improve the wettability of the separator, and can effectively improve the rate and cycle performance of the separator; during coating, the adhesion performance of the coating is improved due to the large number of polar groups on the surface of the separator, which further enhances the ion conductivity of the separator. Moreover, the present invention controls the grafting rate of polyethylene by changing the melt index of polyolefin, thereby achieving a high grafting rate of polyethylene. In other words, the present invention unexpectedly discovered that the polyolefin powder with a melt index between 0.2g / 10min and 1.5g / 10min at 190°C and a load of 21.6kg can improve the liquid absorption effect after swelling and modification. In other words, when the melt index of the polyolefin powder at 190°C and a load of 21.6kg is less than 0.2g / 10min and exceeds 1.5g / 10min, the required liquid absorption effect cannot be achieved. DETAILED DESCRIPTION
[0028] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0029] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0030] The present application relates to a raw material for a high-wettability battery diaphragm and a preparation method thereof. Since the material of the diaphragm is polyethylene and polypropylene, its non-polar characteristics are not conducive to the infiltration of the electrolyte, and thus are not conducive to the preparation of a high-rate, high-capacity, and high-cycle power battery. The traditional method of improving wettability is to improve the performance of the diaphragm by coating a polar material on the surface. However, since the non-polarity of polyolefins is difficult to be compatible with most polar materials, on the one hand, it is not conducive to coating, and on the other hand, it also makes the coating layer easy to detach from the polyolefin diaphragm. To solve these problems, the present application is designed from the raw materials. First, the PE powder is swollen by a swelling agent, and then a large amount of polar substances are grafted on the surface of the polyolefin powder by an initiator. The modified powder is cleaned by water and acetone, and the modified powder is used to prepare the diaphragm. This can improve the wettability of the diaphragm, thereby improving the ionic conductivity of the diaphragm, and then improving the cycle capacity retention rate and rate performance of the battery. At the same time, since the present application introduces polar groups into the molecular chain of polyethylene by chemical grafting, its stability is greatly improved, which is conducive to improving the life of the diaphragm.
[0031] The first embodiment of the present invention proposes a method for preparing raw materials for a highly wettable battery separator, which includes the following steps: mixing a swelling agent with a polyolefin powder, wherein the melt index of the polyolefin powder is 0.2 g / 10 min to 1.5 g / 10 min, and swelling the polyolefin powder to obtain a swollen polyolefin; mixing an initiator and a polar monomer with the swollen polyolefin; and increasing the temperature to graft the polar monomer onto the surface of the swollen polyolefin to form a modified polyolefin. First, the term "melt index" as used herein refers to the extrusion weight of the polyolefin powder at 190°C and 21.6 kg load for 10 min, preferably 0.2 g / 10 min, 0.3 g / 10 min, 0.4 g / 10 min, 0.5 g / 10 min, 0.6 g / 10 min, 0.7 g / 10 min, 0.8 g / 10 min, 0.9 g / 10 min, 1.0 g / 10 min, 1.1 g / 10 min, 1.2 g / 10 min, 1.3 g / 10 min, 1.4 g / 10 min, or 1.5 g / 10 min. Secondly, each step of the present embodiment is described in detail below.
[0032] In the step of mixing the swelling agent with the polyolefin powder, the swelling agent can be added to the polyolefin powder and stirred evenly to make the swelling agent swell the polyolefin powder to obtain the swollen polyolefin. The polyolefin powder can include but is not limited to one or more of polyethylene, polypropylene, polytetrafluoroethylene, polyamide, polyvinyl chloride, polyvinyl difluoride, polyaniline, polyimide, polyethylene terephthalate, and polystyrene; the swelling agent can include but is not limited to one or more of toluene, xylene, and ethyl acetate. In addition, the mass ratio between the polyolefin powder and the swelling agent can be but is not limited to 100: (5 to 50), preferably 100: 5, 100: 10, 100: 15, 100: 20, 100: 25, 100: 30, 100: 35, 100: 40, 100: 45, or 100: 50. In addition, the polyolefin powder may satisfy but is not limited to one or more of the following conditions: a molecular weight of 100,000 to 1,000,000, preferably 100,000, 150,000, 200,000, 250,000, 300,000, 350,000, 400,000, 450,000, 500,000, 550,000, 600,000, 650,000, 700,000, 750,000, 800,000, 850,000, 900,000, 950,000, or 1,000,000; a particle size of 100 to 300 meshes, preferably 100 meshes, 125 meshes, 150 meshes, 175 meshes, 200 meshes, 225 meshes, 250 meshes, 275 meshes, or 300 meshes.
[0033] In the step of mixing the initiator, polar monomer and swollen polyolefin, the initiator and polar monomer can be added to the swollen polyolefin in sequence under stirring. The initiator may include but is not limited to one or more of DCP, BPO, polyvinyl alcohol, ammonium persulfate, and persulfuryl chloride; the polar monomer may include but is not limited to one or more of acrylic acid, maleic anhydride, ethyl methacrylate, hydroxyethyl methacrylate, hydroxybutyl acrylate, and dopamine. In addition, the mass ratio between the polyolefin powder and the initiator can be but is not limited to 100: (0.2 to 5), preferably 100: 0.2, 100: 0.5, 100: 1, 100: 1.5, 100: 2.0, 100: 2.5, 100: 3.0, 100: 3.5, 100: 4.0, 100: 4.5, or 100: 5.0. The mass ratio of the polyolefin powder to the polar monomer may be, but is not limited to, 100:(10 to 100), preferably 100:10, 100:15, 100:20, 100:25, 100:30, 100:35, 100:40, 100:45, 100:50, 100:55, 100:60, 100:65, 100:70, 100:75, 100:80, 100:85, 100:90, 100:95, or 100:100. In addition, in the step of mixing the initiator, the polar monomer and the swollen polyolefin, the dispersant, the initiator, the polar monomer and the swollen polyolefin may be further mixed, and the dispersant, the initiator and the polar monomer are preferably added to the swollen polyolefin in sequence under stirring. The dispersant may include but is not limited to one or more of water, acetone, and white oil. The mass ratio between the polyolefin powder and the dispersant may be but is not limited to 100:(50 to 600), preferably 100:50, 100:75, 100:100, 100:125, 100:150, 100:175, 100:200, 100:225, 100:250, 100:275, 100:300, 100:325, 100:350, 100:375, 100:400, 100:425, 100:450, 100:475, 100:500, 100:525, 100:550, 100:575, or 100:600.
[0034] In the step of increasing the temperature to graft the polar monomer onto the surface of the swollen polyolefin, the polar monomer may be grafted onto the surface of the swollen polyolefin under the conditions of a reaction temperature of 70°C to 110°C and a reaction time of 1h to 5h to form a modified polyolefin. The reaction temperature is preferably 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, or 110°C; the reaction time is preferably 1h, 1h and 20min, 1h and 40min, 2h, 2h and 20min, 2h and 40min, 3h, 3h and 20min, 3h and 40min, 4h, 4h and 20min, 4h and 40min, or 5h. In addition, the grafting rate of the modified polyolefin is defined as:
[0035]
[0036] The grafting rate of the modified polyolefin may be, but is not limited to, 16% to 80%, preferably 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34%, 36%, 38%, 40%, 42%, 44%, 46%, 48%, 50%, 52%, 54%, 56%, 58%, 60%, 62%, 64%, 66%, 68%, 70%, 72%, 74%, 76%, 78%, or 80%.
[0037] In order to remove the impurities that are not reacted or formed during the reaction, the modified polyolefin can be vacuum filtered. In addition, in order to remove the impurities that are not reacted or formed during the reaction, the modified polyolefin can also be washed with water or acetone, and the modified polyolefin can be dried; the drying can be adopted but not limited to drying; the drying temperature is preferably 40°C to 100°C, more preferably 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, or 100°C; the drying time is preferably 1h to 24h, more preferably 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, or 24h.
[0038] The second embodiment of the present invention proposes a raw material for a high-wettability battery separator, which can be formed into a film by coating or extrusion to serve as a battery separator. The raw materials of this embodiment include: modified polyolefins, the modified polyolefins include swollen polyolefins and polar monomers, the polar monomers are grafted on the surface of the swollen polyolefins, and the swollen polyolefins include polyolefin powders, and the melt index of the polyolefin powders is 0.2g / 10min to 1.5g / 10min. In addition, the relevant technical solutions of the modified polyolefins, polyolefin powders and polar monomers mentioned in this embodiment can refer to the contents mentioned in the first embodiment, and will not be repeated here. In addition, the raw materials of this embodiment can be prepared by the preparation method mentioned in the first embodiment, and of course, they can also be prepared by other preparation methods not mentioned, so the raw materials of this embodiment should not be limited by the preparation method mentioned in the first embodiment.
[0039] The present invention is illustrated by the following examples:
[0040] Example 1
[0041] Step 1: Weigh 20 g of xylene and 100 g of polyethylene powder with a melt index of 1.1 g / 10 min, add them into a reaction container, and blend them on a shaker at room temperature for 12 hours to allow the polyethylene to fully swell.
[0042] Step 2: Add 300 g of deionized water into the reaction vessel and heat to 85° C. under nitrogen.
[0043] Step 3: Add 1 g of BPO and 100 g of hydroxyethyl methacrylate into a reaction container, and react at 85° C. under a nitrogen atmosphere for 3 hours to obtain modified PE powder.
[0044] Step 4: Rinse the modified powder after the reaction with deionized water and acetone, and dry it at 80° C. for 8 hours to obtain the purified modified powder.
[0045] Step 5: Take 5 g of the modified powder and press it into a film using a flat vulcanizer at 200°C and 10 MPR.
[0046] Example 2
[0047] The difference between this embodiment and embodiment 1 is that the polyethylene powder used in step 1 has a melt index of 0.95 g / 10 min.
[0048] Example 3
[0049] The difference between this embodiment and embodiment 1 is that the polyethylene powder used in step 1 has a melt index of 0.65 g / 10 min.
[0050] Example 4
[0051] The difference between this embodiment and embodiment 1 is that the polyethylene powder used in step 1 has a melting point of 0.32 g / 10 min.
[0052] Example 5
[0053] The difference between this embodiment and embodiment 1 is that the polyethylene powder used in step 1 has a melting point of 0.25 g / 10 min.
[0054] Example 6
[0055] The difference between this embodiment and embodiment 1 is that the amount of deionized water used in step 2 is 500 g.
[0056] Comparative Example 1
[0057] This comparative example used unmodified PE powder for compression molding.
[0058] Comparative Example 2
[0059] The difference between this comparative example and Example 1 is that acrylic acid is used in place of hydroxyethyl methacrylate in step 3.
[0060] Comparative Example 3
[0061] The difference between this comparative example and Example 1 is that the amount of deionized water used in step 2 is 100 g, and acrylic acid is used in step 3 instead of hydroxyethyl methacrylate.
[0062] Comparative Example 4
[0063] The difference between this comparative example and Example 1 is that the polyethylene powder used in step 1 has a melt index of 0.1 g / 10 min.
[0064] Comparative Example 5
[0065] The difference between this comparative example and Example 1 is that the polyethylene powder used in step 1 has a melting point of 1.6 g / 10 min.
[0066] Grafting rate test
[0067] The weight of the unreacted powder is recorded as M0, and the weight of the reacted powder is recorded as M1. The grafting ratio G is defined as G = (M1-M0) / M0.
[0068] Liquid absorption test
[0069] Cut 5 pieces of film of 40mm x 40mm size, equilibrate the moisture in an oven at 80℃ for 1h, take out and weigh their weight Mx, put the diaphragm into electrolyte and water, keep it sealed and soak for at least 30min, wipe off the surface liquid of the soaked film and test its weight My, the liquid absorption rate A is defined as A=(My-Mx) / Mx.
[0070] Contact angle test
[0071] Cut 5 pieces of film with a size of 10mm x 10mm, equilibrate the moisture in an oven at 80°C for 1 hour, and perform contact angle tests using water and electrolyte respectively using a contact angle tester.
[0072] Please refer to Table 1. It can be seen that as the grafting rate increases, the lyophilicity of the film can be significantly improved, which plays an important role in the film as a high-rate and high-cycle diaphragm. In addition, monomers containing hydroxyl and carboxyl groups significantly improve the polarity of polyethylene. In addition, the PE melt index affects the grafting rate and thus the ability to absorb liquid; more specifically, the PE melt index affects the movement speed of its molecular chain. Too high or too low will affect the reaction speed and thus the grafting rate of the final product.
[0073] Further comparison of Examples 1 to 5 and Comparative Examples 4 and 5 confirms that the PE melt index and the liquid absorption rate do not present a specific positive or negative correlation. Instead, the liquid absorption rate can reach a desired level only within a specific range of PE melt index to meet the desired industrial performance of the separator.
[0074] Table 1
[0075]
[0076]
[0077] The above contents involving common knowledge are not described in detail, and those skilled in the art can understand them.
[0078] The above descriptions are only some specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention shall be included in the protection scope of the present invention. The technical scope of the present invention is not limited to the contents of the specification, but must be determined according to the scope of the claims.
Claims
1. A method for preparing a raw material for a high wettability battery separator, characterized in that: include: Mixing a swelling agent with a polyolefin powder having a melt index of 0.2 g / 10 min to 1.5 g / 10 min, and swelling the polyolefin powder to obtain a swollen polyolefin; mixing an initiator, a polar monomer and the swollen polyolefin; as well as The temperature is increased to allow the polar monomer to be grafted onto the surface of the swollen polyolefin to form a modified polyolefin.
2. The method for preparing the raw material of the high wettability battery separator according to claim 1, characterized in that: The swelling agent includes one or more of toluene, xylene, and ethyl acetate; and / or the polyolefin powder includes one or more of polyethylene, polypropylene, polytetrafluoroethylene, polyamide, polyvinyl chloride, polyvinyl difluoride, polyaniline, polyimide, polyethylene terephthalate, and polystyrene; and / or the initiator includes one or more of DCP, BPO, polyvinyl alcohol, ammonium persulfate, and persulfate chloride; and / or the polar monomer includes one or more of acrylic acid, maleic anhydride, ethyl methacrylate, hydroxyethyl methacrylate, hydroxybutyl acrylate, and dopamine.
3. The method for preparing the raw material of the high wettability battery separator according to claim 1, characterized in that: The step of mixing the initiator, polar monomer and swollen polyolefin further includes: A dispersant, the initiator, the polar monomer and the swollen polyolefin are mixed.
4. The method for preparing the raw material of the high wettability battery separator according to claim 3, characterized in that: The dispersant includes one or more of water, acetone and white oil.
5. The method for preparing the raw material of the high wettability battery separator according to claim 1, characterized in that: The mass ratio between the polyolefin powder and the swelling agent is 100:(5 to 50); and / or the mass ratio between the polyolefin powder and the initiator is 100:(0.2 to 5); and / or the mass ratio between the polyolefin powder and the polar monomer is 100:(10 to 100).
6. The method for preparing a raw material for a high wettability battery separator according to claim 3, characterized in that: The mass ratio between the polyolefin powder and the dispersant is 100:(50 to 600).
7. The method for preparing a raw material for a high wettability battery separator according to claim 1, characterized in that: The molecular weight of the polyolefin powder is 100,000 to 1,000,000; and / or the particle size of the polyolefin powder is 100 mesh to 300 mesh.
8. The method for preparing a raw material for a high wettability battery separator according to claim 1, characterized in that: The grafting rate of the modified polyolefin is 16% to 80%.
9. A raw material for a high wettability battery separator, characterized in that: include: The modified polyolefin comprises a swollen polyolefin and a polar monomer, wherein the polar monomer is grafted onto the surface of the swollen polyolefin, and the swollen polyolefin comprises a polyolefin powder, wherein the melt index of the polyolefin powder is 0.2 g / 10 min to 1.5 g / 10 min.
10. The raw material for a high wettability battery separator according to claim 9, characterized in that: The polyolefin powder includes one or more of polyethylene, polypropylene, polytetrafluoroethylene, polyamide, polyvinyl chloride, polyvinylidene fluoride, polyaniline, polyimide, polyethylene terephthalate, and polystyrene; and / or the polar monomer includes one or more of acrylic acid, maleic anhydride, ethyl methacrylate, hydroxyethyl methacrylate, hydroxybutyl acrylate, and dopamine.
11. The raw material of the high wettability battery separator according to claim 9, characterized in that: The mass ratio between the polyolefin powder and the polar monomer is 100:(10 to 100).
12. The raw material of the high wettability battery separator according to claim 9, characterized in that: The molecular weight of the polyolefin powder is 100,000 to 1,000,000; and / or the particle size of the polyolefin powder is 100 mesh to 300 mesh.
13. The raw material of the high wettability battery separator according to claim 9, characterized in that: The grafting rate of the modified polyolefin is 16% to 80%.
14. A high wettability battery separator, characterized in that: include: A raw material for a highly wettable battery separator according to any one of claims 9 to 13.